Effects of a simulated game on pitching kinematics in youth softball pitcher - Downs, J.; Friesen, K.; Anz, A. W.; Dugas, J. R.; Andrews, J. R.; Oliver, G. D. (International Journal of Sports Medicine, 2020)
Despite evidence that overuse is the most common mechanism of injury, softball pitchers currently have no pitch count regulations. Pain has been associated with certain pitching pathomechanics, and some reports indicate increased pain following a single pitching bout. Therefore, the purpose of this study was to examine trunk and lower extremity kinematics during the first and last inning of a game, as well as last inning pitch volume in youth softball pitchers. Thirty-two youth softball pitchers (12.4±1.6 years, 159.4±8.9 cm, 62.0±13.6 kg) pitched a simulated game. Three fastballs were averaged and analyzed from the first and last inning. Kinematic data were collected at 100Hz using an electromagnetic system, synced with motion analysis software. A Wilcoxon signed rank test revealed pitchers exhibited less trunk rotation toward their pitching arm side in the last inning. A bivariate Pearson`s correlation showed volume of pitches was correlated with stride length (r=0.367, p=0.039) and center of mass (r=0.364, p=0.041) at the start of the pitch, and trunk flexion at top of pitch (r=-0.392, p=0.026), foot contact (r=-0.413, p=0.019), and follow-through (r=-0.436, p=0.013). This study found that pitching a simulated game did result in altered pitching mechanics, meanwhile pitch volume was also correlated with pitching mechanics.